« Vue d’un sling » - Geoff Mains (Genre, Sexualité et Société)
In this text, the narrator is daydreaming in the hospital bed where he is dying from AIDS. A drug-induced hallucination takes him back to a past when he was lying, in the same position, but being fisted in a bathhouse’s sling. The superposition of the hospital world and the leather world allow him to bring face to face the discourse of power and medicine and that of the leather community. In a second-order construction, he is watching the doctor watching him, and from there he can claim, in the face of the discourse of the power that views him as a pervert, the deeper truth of leather brotherhood and love, to which the doctor is blind.